2021
DOI: 10.1021/acs.langmuir.0c02819
|View full text |Cite
|
Sign up to set email alerts
|

Amphipathic Peptide–Phospholipid Nanofibers: Phospholipid Specificity and Dependence on Concentration and Temperature

Abstract: The design of nanoassemblies is an important part of the development of new materials for applications in nanomedicine and biosensors. In our previous study, cysteine substitution of the apolipoprotein A-I-derived peptide 18A at residue 11, 18A­[A11C], bound to 1-palmitoyl-2-oleoylphosphatidylcholine to form fibrous aggregates at a lipid-to-peptide molar ratio of ≤2 and a fiber diameter of 10–20 nm. However, the mechanisms underlying the lipid–peptide interactions that enable nanofiber formation remain unclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Akiba et al reported that cyclohexane solutions of SF form organogels by entanglement of supramolecular nanofibers [ 29 ]. Ikeda et al reported a phospholipid-specific formation of lipid–peptide nanofibers [ 30 ]. These results suggest that the fibrous structures, as shown in Figure 6 , of the DMPC/SF mixture consist of a single structural unit assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Akiba et al reported that cyclohexane solutions of SF form organogels by entanglement of supramolecular nanofibers [ 29 ]. Ikeda et al reported a phospholipid-specific formation of lipid–peptide nanofibers [ 30 ]. These results suggest that the fibrous structures, as shown in Figure 6 , of the DMPC/SF mixture consist of a single structural unit assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the solution was incubated for 1–7 days at 25 °C to evaluate the effects of the spontaneous formation of disulfide bonds in the complex. EDTA was added as a control to inhibit the disulfide bond formation by the chelate formation of residual metal cations in the solution. , We also prepared a solution containing an oxidizing agent K 3 Fe­(CN) 6 to promote disulfide bond formation. In all the conditions of peptide–lipid mixtures prepared, the formation of nanoparticles with a size of approximately 10–20 nm was confirmed by DLS measurements at 25 °C (Figure ).…”
Section: Resultsmentioning
confidence: 99%